The morphological diversity of Mymaridae (Hymenoptera): an atlas of scanning electron micrographs. Part 1. General overview and structure of the head - Huber, John T.; Bolte, Klaus; Read, Jennifer D. (Zootaxa, 2023)
This is the first in a series of studies that aim to provide a comprehensive overview of the morphological diversity of Mymaridae (Hymenoptera), a monophyletic family of small parasitic wasps that are postulated as the sister group of other Chalcidoidea. The external cranial morphology of 65–75 genera and subgenera of Mymaridae (fairyflies) is described and illustrated with almost 430 scanning electron micrographs, including 73 micrographs of the anterior, 68 of the posterior, 75 of the dorsal, 75 of the lateral, and 67 of the ventral views of the head, plus 71 micrographs of the ventral view of the mouthparts. Twenty-one annotated figures illustrate the terms used for morphological structures. Two appendices list the 64 morphological terms and 5 measurements that are defined and illustrated, and the 116 currently recognized valid genera and subgenera of Mymaridae, including collection localities for those that are illustrated. Discussion of head morphology characteristic of Mymaridae is preceded by an overview that includes discussion of best practices for taxonomic descriptions and why these and accurate identifications require well preserved and imaged specimens. Aspects of intraspecific variation, colour, secondary sexual dimorphism, setation (chaetotaxy), surface sculpture and morphometrics are also treated as all of these are often important for describing and distinguishing species. Many of the features illustrated have not previously been used in Mymaridae systematics but may prove to be useful for helping to identify and describe genera and species.